Evaluation of Sinking-In and Cracking Behavior of Soda-Lime Glass under Varying Angle of Trigonal Pyramid Indenter - Yoshida, Satoshi; Wada, Ken; Fujimura, Takahiro; Yamada, Akihiro; Kato, Mitsuo; Matsuoka, Jun; Soga, Naohiro (Frontiers in Materials, 2016)
It is well known that glass undergoes elastic and inelastic deformation under a sharp diamond indenter. Although brittle or less-brittle behavior of glass must be connected with such mechanical responses of glass under the indenter, there has been limited research on in-situ deformation behavior of glass during the loading and unloading indentation cycle. This is because most indentation tests were conducted using a commercial hardness tester for which this information is not available. In this study, the in-situ sinking-in region of glass during indentation test is determined using a custom-designed indentation microscope with trigonal pyramid indenters having different tip angles. It is found that both the shape of contact region and the amount of sinking-in are affected by indenter geometries, and that the projected contact region of the glass sample under Berkovich indenter is not a regular triangle, but a concave triangle with bowed-in edges. This is due to the larger amount of sinking-in under the face than under the ridge of indenter. It is also found that these deformation behaviors of glass are inseparably linked with contact damage or cracking in glass.